Design of ionic-liquid-based hybrid polymer materials with a magnetoactive and electroactive multifunctional response - Fernandes, Liliana C. (2020)
Multifunctional materials with sensor and actuator capabilities are playing an increasing role in modern technology. In this scope, hybrid materials with magnetic sensing and electromechanical actuator response based on magnetic ionic liquids (MILs) and the polymer poly(vinylidene fluoride) (PVDF) have been developed. MILs comprising different cation alkyl chain lengths [Cnmim]+ and sharing the same anion [FeCl4] - were incorporated at 20% wt. into the PVDF matrix and the morphological, physical-chemical and functional properties of the materials evaluated. Increasing IL alkyl chain length leads to the formation a porous structure , together with an increase in the electroactive PVDF β phase content of the polymer and a decreasing in the crystallinity degree and the thermal stability. The magnetic susceptibility of the [Cnmim][FeCl4] - /PVDF films reveals a paramagnetic behavior. The multifunctional response is characterized by a magnetoionic response that decreases with increasing IL alkyl chain length, being the highest magnetoionic coefficient (1.06±0.015 V cm1 Oe-1 ) observed for [C2mim][FeCl4]/PVDF. The electromechanical actuator response is characterized by a highest displacement of 2.2 mm for the [C4mim][FeCl4]/PVDF film by applying a voltage of 4 V at a frequency of 100 mHz. Further, their solution processing makes those multiresponsive materials compatible with additive manufacturing technologies.